Arabic Language Learning Technology in the First Cycle of Basic Education/تكنولوجيا تعلّم اللغة العربية في الحلقة الأولى من التعليم الأساس - Kurniadi, Fakhar (Nurul Jadid University, 2017)
The educational media and technologies are: materials and tools that are partially or wholly employed in school education to create learning. The school, the teacher, the spoken word, the book, the picture, the slide, the film, the computer, the expert, etc., Educational tools and technology are important to guide students' formal education and production. Education technology is a practical method of thought, with an integrated base of actors. Educational means are part of educational techniques or educational technology. Educators say: